Determination of one dimensional model of speed in Colombian Central West using local seismic tomography (Revista de Investigaciones Universidad del Quindío, 2013)
A general one-dimensional velocity model was determined using the arrival times of P waves, and three models for seismic zones called Eje Cafetero, Tolima and Subduction, allowing thus a better location of seismic events found in the study area limited to the quadrant defined as longitude 76.7 ° W 74.5 ° W and latitude 4.0° N to 5.8° N. The events were provided by the National Seismic Network of Colombia (NSNC, Ingeominas), the Volcanological and Seismological Center of Manizales (CVSM) and the Seismological Observatory at University of Quindío (SOQ). Using the Wadati method, a relationship Vp/Vs=1.771 was determined. For the study zone, 3349 events were located using the software SEISAN and the non-linearized ray inversion method of VELEST . Welllocated events, with GAP
Keywords: non-linearized ray inversion; VELEST; one-dimensional velocity model; Seismic rays; P and S waves